An Arctic ecosystem : the coastal tundra at Barrow, Alaska - Brown, Jerry; Miller, Philip C.; Tieszen, Larry L.; Bunnell, Fred (Dowden, Hutchinson & Ross, Inc., 1980)
From the Foreward: This book is one of a series of volumes reporting results of research by U. S. scientists participating in the International Biological Program (IBP). As one of the 58 nations taking part in the IBP during the period July 1967 to June 1974 , the United States organized a number of large, multidisciplinary studies pertinent to the central IBP theme of "the biological basis of productivity and human welfare." Direct financial support of the Biome-wide program was derived from three major sources: the National Science Foundation, the State of Alaska and the petroleum industry through the University of Alaska. The NSF funding was under the joint sponsorship of the U. S. Arctic Research Program (Division of Polar Programs) and the U. S. International Biological Program (Ecosystem Analysis). The Army Research Office and the Department of Energy (previously AEC and ERDA) both contributed funded projects to the Program. Industry support was provided through unrestricted grants from: Atlantic Richfield Company, Alyeska Pipeline Service Company, BP Alaska, Inc. Cities Service Company, Exxon Company, USA (Humble Oil and Refining Company), Gulf Oil Corporation , Marathon Oil Company, Mobil Oil Company, Prudhoe Bay Environmental Subcommittee of the Alaska Oil and Gas Association, Shell Oil Company, Standard Oil Company of California, Standard Oil (Indiana) Foundation Inc., and Sun Oil Company.